EXPLORING VIDEO-GAME PRODUCTION’S CONTINGENCY ON LIVE-STREAMING PLATFORMS: THE CASE OF TWITCH - Papaevangelou, Charilaos; Roinioti, Elina (AoIR Selected Papers of Internet Research, 2021)
This article studies the cultural contingency of video-game production on Amazon’s live-streaming platform, Twitch. It looks at this phenomenon from a political-economic perspective to unearth Twitch’s platformisation strategy to better understand what it means for the video-game industry. Platformisation signifies the infrastructural embeddedness of platforms, supported by a business strategy of expanding beyond their services’ boundaries to standardise appropriation, processing and exploitation of data, resulting in a dependency of content creators on digital platforms. Subsequently, we wish to grasp what dependencies are created and how it is made possible. We argue that Twitch is transforming into an integral part of the video-game production cycle by expanding its services to every stage of a game’s life cycle. Consequently, game developers are incentivised to apply these features in their game design, thus creating an economic feedback loop that a) aspires to increase user acquisition, retention and revenue, b) locks-in game developers and viewers alike, and c) “platformises” the gaming experience.